Dialogue Between Ukrainian and European Cultural Values as a Prerequisite for Ukraine’s Sustainable Development: Faith and Fear Versus Stability and Chaos - Dodonova, Vira; Aleksandrova, Olena; Binkivska, Kristina; Dodonov, Danylo; Voinarovska, Liudmyla; Zabolotniuk, Volodymyr; Patlaichuk, Oksana; Klose, Ronny (European Journal of Sustainable Development, 2025)
This article presents a comparative analysis of European and Ukrainian cultural values in the context of Ukraine’s sustainable development. The aim is to identify both the similarities and the differences between the cultural value systems of Ukraine and Europe. The concept of value is explored through a multidisciplinary lens, incorporating definitions from dictionaries and monographs, and further supported by the analytical capabilities of artificial intelligence. The study outlines a complex system of values, including existential (meaning-of-life), vital, interactional, and socialization-oriented dimensions. In addition to commonly recognized European values such as freedom, democracy, and equality, other important concepts are highlighted: inner world, profound respect for ordinary life, self-realization, acceptable difference, and pragmatic rationalism as mastery over the world. The analysis of Ukrainian values emphasizes concepts such as aspiration for harmony, warm-heartedness and emotional openness, love of freedom, deep connection with the environment, a sense of shared responsibility for others, and resilience in overcoming geopolitical traumas. Special attention is given to the opposition between secularism and religion as two distinct frameworks for organizing cultural space. Secular culture is examined as a worldview grounded in rationality and the public sphere, in contrast to the sacred and faith-based dimensions of traditional religiosity. Faith and fear are interpreted as both internal emotional drivers and societal forces that shape the perception of chaos and order. Ukrainian cultural values are presented as an open and evolving system, capable of integrating new elements while preserving national identity. The article concludes, through a comparative table of core values, that Ukrainian and European cultural systems share fundamental affinities, affirming Ukraine’s integral place within the European community. Keywords: intercultural communication, sustainable development, value system, Europe, European cultural values, Ukraine, Ukrainian cultural values, value dialogue, secularism, religion, faith, fear.